THE EFFECT OF ADDITION OF FLY ASH AND LASER RADIATION ON CARBON BASED ELECTRODE FOR ANALYSIS OF DOPAMINE IN THE MIXTURE WITH ASCORBIC ACID USING VOLTAMMETRY - Sri Rahayu, Ria
Dopamine (DA) is a catecholamine compound which plays an important role as a neurotransmitter in the central nervous system. DA levels are related to several diseases such as Schizophrenia and Parkinson. Consequently, the determination of DA and related cathecolamines is necessary in neurochemistry and brain science studies. Therefore, the development of an accurate, fast, and simple method for the determination of DA becomes very important.